Behavior of the flux-flow resistivity in mesoscopic superconductors - Sanchez Lotero, Pedro Nel (2014)
In this work we solved the time dependent Ginzburg-Landau equations numerically finding profiles of the flux-flow resistivity for different widths of superconducting stripes. We found vortex pinning induced by the surface superconductivity. This pinning avoids the movement of the vortex lattice preventing the generation of a voltage. We also found the existence of a mesoscopic region where the flux-flow resistivity shows size effects and we observed a transition to a macroscopic regime as the width increases. © 2014 Elsevier B.V. All rights reserved.